Exchange Rate and Output Dynamics Between Japan and Korea - Sammo Kang; Soyoung Kim; Yunjong Wang; Deok Ryong Yoon (Hamburg Institute of International Economics (HWWA), 2003)
Japan and Korea are close countries in terms of economic interaction as well as geography. To quantify the impact of changes in the yen-dollar exchange rate on the Korean economy before and after the crisis in 1997, the sample period has been divided into two sub-periods and the causal relationships examined by using vector autoregression analysis. Our estimates show that while the response of Korean industrial production to changes in the yen-dollar exchange rate was not significant during the pre-crisis period, it became significant during the post-crisis period. The forecast error variance decomposition also confirms that the yen-dollar exchange rate shocks have almost negligible explanatory power with regards to Korean industrial production during the pre-crisis period, but they have some significance for the postcrisis period. These empirical results show that the free floating exchange rate regime adopted since the crisis cannot insulate the Korean economy from external nominal shocks such as the yen-dollar exchange rate shocks.
Keywords: F41; E32; F36; 330; Wechselkurs; Wechselkurssystem; Schock; Konjunkturzusammenhang; Industrielle Produktion; Schätzung; Japan; Südkorea